The Perfection of Interpreting By Non-Linguist Interpreters - Yulianti, Ni Ketut Dewi (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
An interpreter is a person who converts a thought or expression in a source language into an expression with a comparable meaning in a target language in real time. The function of interpreters is to convey every semantic element (tone and register) and every intention and feeling of the message that the source-language speaker is directing to target-language recipients. Interpreting (oral translation) is not an easy job. In written translation, a translator has time to consider and revise each word and sentence before delivering their product to the client. While an interpreterâs goal is to achieve total accuracy at all times, details of the original (source) speech can be missed and interpreters can ask for clarification from the speaker. This paper deals with the perfection ofÂ  interpreting by non-linguistÂ  interpreters in Bhagawad Gita class in Sri Sri Jaganath Gaurangga Temple in Denpasar, and it has been presented in 2ndTranscon (International Translation Conference) in Jakarta, but hasnât been published yet. There are some interpreters at the temple that have no special background knowledge about linguistics, especially translation / interpreting, but they can deliver the message from the source language (SL) English into the target Language (TL) Indonesian perfectly. The cross-culture understanding that they have and their knowledge background about the text (Bhagavad Gita) play an important role in this case. The interpreters have been interviewed for the purpose of this paper to find out the factors that affect the perfection of interpreting for non-linguist interpreters.